2020
DOI: 10.1002/ldr.3595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of engineered nanoparticles on soil biota: Do they improve the soil quality and crop production or jeopardize them?

Abstract: Nanoscience and nanotechnology have been shown to have the capacity to help study, manipulation,design, and synthesis of new nano-sized materials to manufacture new products with desirable features never seen before. The unique properties of materials at nanoscale opens an excellent possibility for nanotechnology to be used in soil environmental remediation, and water, and air decontamination. In crop management, nanomaterials are used to regulate the controlled release of nutrients, fertilizers, and pesticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 139 publications
(198 reference statements)
0
14
0
Order By: Relevance
“…Different to endogeic earthworms, the rest of the organisms found have an epigeal habit, i.e., they live on the soil surface (leaf litter), to this group belong spiders, ants, centipedes, and some predatory beetles, among others ( Huerta et al., 2008 ). The review by Pérez-Hernández et al. (2020) reported contradictory cases of effects of different metallics NPs on microfauna, mesofauna, macrofauna, and edible and inedible plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different to endogeic earthworms, the rest of the organisms found have an epigeal habit, i.e., they live on the soil surface (leaf litter), to this group belong spiders, ants, centipedes, and some predatory beetles, among others ( Huerta et al., 2008 ). The review by Pérez-Hernández et al. (2020) reported contradictory cases of effects of different metallics NPs on microfauna, mesofauna, macrofauna, and edible and inedible plants.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, due to the increased of NMs, the release into environmental systems is inevitable, representing a concern for scientists, technologists since it could be an emerging ecological contaminant ( Avila-Arias et al., 2019 ). Besides, ordinary people have also shown concerns regarding the unregulated use of engineering nano-sized materials or devices ( Pérez-Moreno et al., 2019 ; Pérez-Hernández et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, in parallel to positive effects, it is worthy to also address potential or proved negative effects of nanomaterials applied through foliar or soil routes on plant-associated soil microorganisms [ 92 ]. However, the literature curation showed a contradictory trend in results and claimed even more in-depth investigations to get insights into the biological conversion and ENPs-plant-soil-microorganisms relationship [ 93 ]. Till now, various nano-based particles and materials, including organic and inorganic NPs, metal and metal oxides, CNTs, biochar, and biochar-based nanocomposites, graphene nanomaterials, quantum dots, have been used in the agricultural system whose pathogenic and antimicrobial behavior has been systematically well documented, however, the interactions of nanomaterials with soil microorganisms affecting food production are still poorly explored [ 94 ].…”
Section: Nanomaterials and Soil Microorganism’s Interactionsmentioning
confidence: 99%
“…The use of engineering nanoparticles (ENPs) for soil decontamination has been highlighted due to surface modification chemistry and physical parameters of ENPs, which offer significant advantages compared to conventional methods for addressing environmental contamination (Rathor et al 2017;Tafazoli et al 2017;Cecchin et al 2017;Feizi et al 2018). For instance, as a country, Mexico has made progress and contributed to the generation of knowledge on environmental contamination caused by NPs in agriculture and natural soil (Delgado-Ramos 2014;Pérez-Hernández et al 2020;Pérez-Moreno et al 2019). In other countries as China, researchers have proposed the TiO 2 NPs in the decontamination of heavy metals (Cd, As, Pb, and others) in association with plants of maize (Lian et al 2020), rice (Zhang et al 2020;Wu et al 2021), wheat (Wu et al 2020), among others.…”
Section: Introductionmentioning
confidence: 99%
“…In Zea mays L, Bouguerra et al (2018) showed that the TiO 2 (1000 mg kg −1 ) was not toxic when added to natural soil. Due to these examples and other cases, controversies continue regarding the positive, adverse, and null effects in different plant species (Pérez-Hernández et al 2020).…”
Section: Introductionmentioning
confidence: 99%